Influence of the banded Herbst appliance on dental changes in mixed dentition - Sampaio, Luana Paz; Raveli, Dirceu Barnabé [UNESP]; Santos-Pinto, Ary dos [UNESP]; Landázuri, Denise Rocha Goes; Maia, Savana de Alencar (Dental Press International, 2012)
OBJECTIVE: This prospective clinical study was conducted with the purpose of evaluating the influence of the banded Herbst appliance on dental changes during the early treatment of Class II malocclusion. METHOD: The sample consisted of 15 prepubertal subjects (12 boys and 3 girls, initial age: 9 years and 6 months) who were treated with the Herbst appliance. Treatment effects were compared with those of a Class II Division 1 group of 15 subjects (8 boys and 7 girls, mean initial age 9 years and 1 month), not treated orthodontically. Statistical analysis was performed using Student t-test with 5% significance level. RESULTS: The results showed that treatment with the banded Herbst appliance in the mixed dentition stage tended to upright maxillary incisors (mean: 4.14°). The maxillary molars were distalized and intruded significantly (mean 2.65 mm and 1.24 mm, respectively), the lower incisors slightly protruded anteriorly (mean 1.64 mm) and the molars showed no significant changes in the horizontal and vertical directions. Furthermore, significant improvements were noted in overbite (1.26 mm), overjet (4.8 mm) and molar relationship (12.08 mm). CONCLUSIONS: Changes in the upper dental arch were found to be greater than changes in the lower arch. Furthermore, mandibular anchorage loss was reduced due to the anchorage system used in the study.
Influência do aparelho de Herbst bandado sobre as alterações dentárias na dentição mista
Keywords: Herbst appliance; Anchorage system; Mixed dentition; Orthodontics; Cephalometry